Soluções sólidas de quartzo co-recheadas com expansão térmica zero por síntese sol-gel - Fonseca, Beatriz Paiva da (Universidade Federal de São Carlos, 2023)
First of all, I would like to thank my family for all the love: my mother Conceição, who always invested in my education, my father Walter, who always gave me courage, my sister Amanda, who is my partner and my balance, and my boyfriend Enzo, who is my supporter and role model. I have also always been graced with good friends. Many thanks to my great friends from the beginning of my degree in Belo Horizonte Luis and Juliana (and also Arthur), whose friendship always went far beyond studies and overcame distance for years, my friends at UFSCar Carol, Franzin, Kaue, Paloma, Martinez and Pedro and all the others from the group "Primas Mancilha", and in São Carlos, Senise e Gagui, and my dear ex-roommate and professional advisor Barbara. During my graduation I had the privilege of taking classes and being guided by great educators and professionals, whom I admire so much. I gratefully acknowledge Rosario Suman Bretas, my first advisor, and Edgar Dutra Zanotto, my advisor for this work and who made it possible for me to realize one of my greatest dreams. I would like to thank my advisors in Germany Joachim Deubener and Gundula Helsch for all the attention and knowledge taught to me, and also all my work colleagues at INW and at LaMaV, for their support. Finally, I would like to thank all the people who have in some way cheered my success or contributed to my education.
Co-stuffed quartz solid solutions with zero thermal expansion by sol-gel synthesis
Keywords: Síntese por sol-gel; Expansão térmica; Soluções sólidas de quartzo; Aluminossilicato de lítio; Cobalto; Thermal expansion; Quartz solid solutions; Lithium aluminosilicate; Cobalt; Sol-gel synthesis; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS